Modern Solutions To The Origin Of Arrhythmia As A Symptom Of Various Diseases - Turayev Hikmatillo Negmatovich (Journal of Science in Medicine and Life, 2024)
Arrhythmia is a pathological condition in which heart rate, rhythm and sequence of heart contractions are disturbed. This is the general name of pathology, which is characterized by any deviation from the normal state of the heart. There are several types of arrhythmia, each of which has its own symptoms and causes. Let's take a closer look at what arrhythmia is, how it manifests itself, how many types there are, and how to treat them. Arrhythmia attacks can occur in both young and old age. Of course, adults are more prone to heart problems, but even children suffer from arrhythmias. Pathology can be congenital or acquired. The second type is more common. Normal heart rate is 60-80 beats per minute. With changed indicators, arrhythmia develops, which can lead to harmful consequences.